The physiological function of α-ketoglutarate acid and its research advances in stomatology - CHENG Chunan; HU Dandan; KANG Feiwu (Kouqiang hemian waike zazhi)
α-ketoglutarate (AKG) is an essential intermediary metabolite of the tricarboxylic acid (TCA) cycle and amino acid metabolism. By participating in the generation of adenosine-triphosphate (ATP) and the biosynthesis of a variety of important amino acids and proteins, it is widely involved in a series of important physiological processes. Since there are few reports on the research of AKG in stomatology, this paper reviews the physiological function of AKG and its research advances in stomatology, which may lay a theoretical foundation for broadening the application of AKG in stomatology.